Gene dosage effects of poly(A) track-engineered hypomorphs - Geralle Powell; Slavica Pavlovic Djuranovic; Sergej Djuranovic (Elsevier, 2021)
Manipulation of gene activity through creation of hypomorphic mutants has been a long-standing tool in examining gene function. Our previous studies have indicated that hypomorphic mutants could be created by inserting cis-regulatory sequences composed of consecutive adenosine nucleotides called poly(A) tracks. Here we use poly(A) tracks to create hypomorphic mutants and functional characterization of membrane, secretory, and endogenous proteins. Insertion of poly(A) tracks into the sequences of interleukin-2 and membrane protein CD20 results in a programmable reduction of mRNA stability and attenuation of protein expression regardless of the presence of a signaling sequence. Likewise, CRISPR-Cas9 targeted insertion of poly(A) tracks into the coding sequence of the endogenous human genes AUF1 and TP53 results in a programmable reduction of targeted protein and mRNA levels. Functional analyses of AUF1-engineered hypomorphs indicate a direct correlation between AUF1 gene levels and the stability of AUF1-regulated mRNAs. Hypomorphs of TP53 affect expression of the target genes differentially depending on the severity of the hypomorphic mutation. Finally, decreases in TP53 protein affect the same cellular pathways in poly(A) track-engineered cells as in cancer cells, indicating these variants' biological relevance. These results highlight this technology's power to create predictable, stable hypomorphs in recombinant or endogenous genes in combination with CRISPR-Cas9 engineering tools.